KESEMBUHAN, PENEBUSAN, DAN KEBAIKAN ALLAH DALAM TEOLOGI PENTAKOSTAL - Minggus Minarto Pranoto (Sekolah Tinggi Theologia Abdiel, 2017)
This paper is about to criticize the Pentecostal theology about the healing. The theology believe that the miracle of healing can happen because Jesus died on the cross. He was able to heal all sicknesses and to free people from the shackles of the devil. Furthermore, the concept of God is a good God also used to refer to the belief that God has a strong desire to heal. But in reality, many Christians experience sickness is not healed. So the doctrine of the Pentecostal healing actually makes conflicted for people who have never experienced the healing of sickness, although he has been obedient and trust in the Lord. The author tries to reconstruct the Pentecostal theology of healing that could accommodate such a struggle. At the end of writing the author makes a conclusion that in sickness and suffering severe, the work of the Holy Spirit as the agent of transformative Suffering can not be separated from his work as the agent of the transformative life. The Holy Spirit as the agent of transformative Suffering can wear sickness and suffering experienced by believers to proclaim the work of his reform, which is a new birth. The new birth here interpreted as the transformation of the Holy Spirit in their lives so that their lives can sincerely declare lives according to the values of the Kingdom of God which contains joy, faithfulness, patience, love, truth, peace. These values are stronger than mere physical healing function experienced by a person.